Critical parameters for integrating co-composting of POME and EFB into life cycle assessment models of palm oil production. - Victor Baron; Mohamed Saoud; Joni Jupesta; Ikhsan Rezky Praptantyo; Hartono Tirto Admojo; Cécile Bessou; Jean-Pierre Caliman (Indonesian Journal of Life Cycle Assessment and Sustainability, 2019)
Palm oil mill’s co-products (empty fruit bunch – EFB and palm oil mill effluent – POME) management is a matter of concern in Indonesia. Co-composting is a promising waste management practice that would allow a reduction of environmental impact and a restitution of organic matter to the soil. This study is a part of a Life Cycle Assessment (LCA) project and aims to pinpoint the most environmentally impacting compartments of the palm oil production chain. It deals more specifically with the Life Cycle Inventory of data on the composting process based on site specific data. Data on the recycled biomass, energy demand and yielded compost properties were recorded in an industrial palm oil mill over one year. Due to the local conditions, high nutrient leaching from the compost were recorded and the compost remained very wet and hot (thermophilic phase). The composting process only led to 40% of methane avoidance compared to anaerobic digestion of POME, and the global nutrient recovery efficiency was below 50%. We identified the following critical parameters to increase environmental benefits from composting:      i) the POME/FFB ratio from the mill ii) the roofing of the composting platform, iii) the POME/EFB ratio, iv) the turning frequency, v) the recycling of leachates and vi) the process duration and drying period. The nutrient recovery and the doses of compost applied in the field depend on all of those inter-connected parameters. The data presented will be used within LCA models to assess net environmental benefits from various POME and EFB co-composting systems.